Applied Analysis of Composite Media : Analytical and Computational Results for Materials Scientists and Engineers /: Analytical and Computational Results for Materials Scientists and Engineers. (2019) - Drygaś, Piotr; Gluzman, Simon; Mityushev, Vladimir; Nawalaniec, Wojciech
No abstract available